A study on the nitrogen removal efficacy of bacterium Acinetobacter tandoii MZ-5 from a contaminated river of Shenzhen, Guangdong Province, China. (November 2020) - Ouyang, Liao; Wang, Keju; Liu, Xinyue; Wong, Ming Hung; Hu, Zhangli; Chen, Huirong; Yang, Xuewei; Li, Shuangfei
Graphical abstract: Highlights: Strain MZ-5 showed heterotrophic nitrification and aerobic nitrification capability. Ammonium was the priority nitrogen source in the mixed N sources. nap A gene was successfully amplified. Strain MZ-5 showed good nitrogen removal performance when treating wastewater. Abstract: Heterotrophic nitrification–aerobic denitrification (HN-AD) has advantages over the traditional nitrogen removal process when removing multiple types of nitrogen in wastewater treatment. Acinetobacter tandoii MZ-5, which is capable of HN-AD, was isolated from the sediment of a polluted river for the first time. It used NH4 + -N, NO2 – -N and NO3 – -N as sole nitrogen sources with maximum removal rates of 2.28, 1.18 and 1.04 mg L −1 h −1, respectively. Simultaneous nitrification and denitrification were observed when using mixed N sources and NH4 + -N was preferentially utilized. High nitrogen removal efficiencies (>90%) were achieved under the following conditions: C/N ratio 11–18, pH 6–8, 25–30 °C and dissolved oxygen 7.35–7.66 mg L −1 . Strain MZ-5 was effective at treating wastewater from landfill leachate treatment plants, with NH4 + -N, NO3 – -N and total nitrogen (TN) removal efficiencies of 99.28%, 44.85% and 45.31%, respectively. Thus, strain MZ-5 may be a good candidate for wastewater treatment.